Functionalization of SBA-15 mesoporous materials using ``thiol-ene click'' michael addition reaction - Kumari, Sushma; Malvi, Bharmana; Ganai, Anal Kumar; Pillai, Vijayamohanan K.; Sen Gupta, Sayam (Journal of Physical Chemistry C, 2011)
Methacrylate-labeled SBA-15 has been successfully synthesized from calcined SBA-15 and commercially available 3-trichlorosilyl propylmethacrylate. This material undergoes efficient thiol-ene ``click reaction'' with a variety of both thiol and disulfide-containing substrates in aqueous and organic media. The products were thoroughly characterized by a variety of analytical techniques including multinuclear (C-13, Si-29) solid-state NMR, TG-DTA, and nitrogen adsorption desorption studies. Disulfide-containing substrates in which the TCEP-mediated reduction of the disulfide bond and its subsequent addition to the methacrylate group anchored in SBA-15 in one-pot were used to synthesize a silica-protein hybrid material composed of biotin-labeled SBA-15 and streptavidin. Electrochemically active material was synthesized from the reaction of ferrocene-containing thiol and the methacrylate-labeled SBA-15. The ease of synthesis for the methacrylate-labeled SBA-15 material together with its ability to undergo efficient chemoselective thiol-ene reaction would make it a very attractive platform for the development of covalently anchored enzymes and sensors.